Landowners’ Rights and Criminal Liability: Towards a Normative Framework for International Legal Protection - Ary Nizam; Md. Shodiq; Supaphorn Akkapin (CV. Era Digital Nusantara, 2025)
Land ownership has long been seen as a fundamental right, but its protection under international law remains fragmented and inadequate. While the Universal Declaration of Human Rights and related covenants recognize the property right, there is no comprehensive international instrument explicitly safeguarding land rights, especially amid systematic land grabbing and forced evictions. This study employs a normative legal approach with a qualitative design, analyzing primary legal sources—including international treaties, jurisprudence from the International Court of Justice and the International Criminal Court—as well as academic literature and reports from civil society. The findings highlight three main points. First, international recognition of land rights is weak and lacks effective enforcement mechanisms. Second, systematic violations like mass evictions could be considered international crimes, particularly crimes against humanity, but the lack of explicit jurisprudence creates interpretive ambiguity. Third, while states often justify large-scale land dispossession, corporate accountability at the international level remains limited because it relies on non-binding soft law principles. Reflecting on these findings, the study advocates for the development of a normative framework that links land rights protection with international criminal responsibility. Such a framework would not only strengthen theoretical understanding by connecting property rights with international criminal law but also offer practical guidance for policymakers, international organizations, and civil society. Ultimately, this research aims to help bridge the gap between formal recognition and absolute protection of land rights in the context of globalization.